Konstruksi Verba Serial Direksional pada Bahasa Dayak Ngaju Kalimantan Tengah - Dina Lutfiana Putri; Agus Subiyanto (Universitas Mulawarman, 2023)
Dayak Ngaju is one of the many Indonesian languages ​​originating from the Austronesian family. Dayak Ngaju language is used by speakers from Central Kalimantan. This study aims to determine the continuous directed verbal constructions in the Dayak Ngaju language based on a typology study and then compare it with Balinese. This type of research is descriptive qualitative. Methods of data collection using the interview method are also considered. The typological approach used as data analysis in this study is then presented through an informal method. The results of this study indicate that the Dayak Ngaju language can be formed through transitive Verba 1 (V1) + transitive Verba 2 (V2) and intransitive Verba 1 (V1) + intransitive Verba 2 (V2) patterns. If related to the Talmy typology, the results of the study show that Dayak Ngaju is a language that has a verb or satellite framework, which is different from Balinese which may be formed based on motion verbs (as core verbs) and followed by prepositional phrases (roads) which act as addition.